2004
DOI: 10.1080/00288306.2004.9515093
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating cool‐water from warm‐water carbonates and their diagenetic environments using element geochemistry: The Oligocene Tikorangi Formation (Taranaki Basin) and the dolomite effect

Abstract: Fields portrayed within bivariate element plots have been used to distinguish between carbonates formed in warm-(tropical) water and cool-(temperate) water depositional settings. Here, element concentrations (Ca, Mg, Sr, Na, Fe, and Mn) have been determined for the carbonate fraction of bulk samples from the late Oligocene Tikorangi Formation, a subsurface, mixed dolomite-calcite, cool-water limestone sequence in Taranaki Basin, New Zealand. While the occurrence of dolomite is rare in New Zealand Cenozoic carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…9) for the studied samples plot along with the Cenozoic New Zealand carbonates (but on the higher side of the Mn, Mg and Na) indicating their genesis in a temperate cooler waters but in actual condition the MVI (Lesser Antilles) is located in the zone of tropics which is a known latitudinal tectonic setting. Here we report a deviation from the general observation of Winefield et al(1996); Rao (1991), Hood et al(2004 and Azizi et al (2014) on the temperate limestones, although the geochemical parameters and ratios as mentioned above satisfy the discrimination. The authors also suggested that the regional generalisations can be made limited to the skeletal differences, diagenetic process involved etc., Based on the above and analysed data sets of the studied samples, the net effect of volcanogenesis, carbonate dilution and dissolution play an important role in discriminating the carbonates of tropical origins.…”
Section: Contamination and Diagenetic Alterationscontrasting
confidence: 72%
“…9) for the studied samples plot along with the Cenozoic New Zealand carbonates (but on the higher side of the Mn, Mg and Na) indicating their genesis in a temperate cooler waters but in actual condition the MVI (Lesser Antilles) is located in the zone of tropics which is a known latitudinal tectonic setting. Here we report a deviation from the general observation of Winefield et al(1996); Rao (1991), Hood et al(2004 and Azizi et al (2014) on the temperate limestones, although the geochemical parameters and ratios as mentioned above satisfy the discrimination. The authors also suggested that the regional generalisations can be made limited to the skeletal differences, diagenetic process involved etc., Based on the above and analysed data sets of the studied samples, the net effect of volcanogenesis, carbonate dilution and dissolution play an important role in discriminating the carbonates of tropical origins.…”
Section: Contamination and Diagenetic Alterationscontrasting
confidence: 72%
“…Sr concentration and mineralogy composition of carbonates have a direct relationship, as Sr values increase with aragonite increase and decrease with calcite increase (Rao & Adabi, 1992; Rao & Amini, 1995; Rao, 1996; Adabi, 2004). Sr values range from 8000 to 10 000 ppm in recent tropical bulk carbonate samples (Milliman, 1974), while in recent temperate bulk carbonates it reduces and ranges from 1500 to 4500 ppm (Rao, 1991; Rao & Adabi, 1992; Hood, Nelson & Kamp, 2004). The values of Sr in low-Mg calcite, high-Mg calcite and aragonite are 1000 ppm, 3000 ppm and up to 10 000 ppm, respectively (Kinsman, 1969; Carpenter & Lohmann, 1992; Rao, 1996; Rao et al 1998).…”
Section: Original Carbonate Mineralogymentioning
confidence: 99%
“…, ). Sr concentration also has a direct relation with increasing water temperature (Hood, Nelson, & Kamp, ; Morse & Mackenzie, ; Winefield, Nelson, & Hodder, ). Although aragonite recrystallization results in Sr loss (Brand & Veizer, ), but limestones with aragonite origin have naturally higher concentration than those with calcite origin (Veizer & Demovic, ).…”
Section: Lithological Geochemical and Faunal Paleoclimate Proxies Imentioning
confidence: 99%
“…The Sr content in recent tropical bulk carbonates ranges from 8,000 to 10,000 ppm (Milliman, 1974;Rao, Amini, & Ferguson, 1998), while in recent temperate carbonate it ranges from 1,600 to 5,000 ppm (Rao & Amini, 1995;Rao & Jayawardane, 1994;Rao et al, 1998). Sr concentration also has a direct relation with increasing water temperature (Hood, Nelson, & Kamp, 2004;Morse & Mackenzie, 1990;Winefield, Nelson, & Hodder, 1996). Although aragonite recrystallization results in Sr loss (Brand & Veizer, 1980), but limestones with aragonite origin have naturally higher concentration than those with calcite origin (Veizer & Demovic, 1974).…”
Section: Bauxitementioning
confidence: 99%